2021
DOI: 10.21203/rs.3.rs-432815/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early immune pressure imposed by tissue resident memory T cells sculpts tumour evolution in non-small cell lung cancer

Abstract: Tissue-resident memory T cells (TRM) provide immune defence against local infection and can inhibit cancer progression. However, it is unclear to what extent chronic inflammation impacts TRM activation and how the immune pressure exerted by TRM affects developing tumours in humans. We performed deep profiling of lung cancers arising in never-smokers (NS) and ever-smokers (ES), finding evidence of enhanced TRM immunosurveillance in ES lung. Only tumours arising in ES patients underwent clonal immune escape, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…37 Further, studies have also shown that the coexpression of CD4 and CD 69 aid in metastatic lung cancer progression and helps in the immune escape by delaying the immune pressure in patients diagnosed with lung cancer. 38 In CSCAT, we observe that the coexpression of CD69 with CD8 is predominant. The relative expression of CD8 and CD69 are −0.24 and −0.26 in primary lung cancer-associated T cells and −0.83, 0.86 in metastatic lung cancer-associated T cells, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…37 Further, studies have also shown that the coexpression of CD4 and CD 69 aid in metastatic lung cancer progression and helps in the immune escape by delaying the immune pressure in patients diagnosed with lung cancer. 38 In CSCAT, we observe that the coexpression of CD69 with CD8 is predominant. The relative expression of CD8 and CD69 are −0.24 and −0.26 in primary lung cancer-associated T cells and −0.83, 0.86 in metastatic lung cancer-associated T cells, respectively.…”
Section: Resultsmentioning
confidence: 81%